Procedure for Submitting Value Added Tax (VAT) Restitution for the December 2023 Tax Period at PT CMT - Afifah, Astianur Arizahro; Mulyadi , Roza; Pratiwi, Refi (Journal of Applied Business, Taxation and Economics Research, 2025)
Excess Tax occurs when the creditable input tax is greater than the output tax, the difference is an excess tax that can be compensated to the next tax period or can be submitted for refund (restitution) at the end of the fiscal year. PT CMT experienced an overpayment of Value Added Tax (VAT) in the December 2023 period and filed a restitution. The purpose of this writing is to understand how the procedure for filing Value Added Tax (VAT) restitution at PT CMT and to find out what obstacles occur during the process of filing Value Added Tax (VAT) restitution carried out by PT CMT. This writing method uses a descriptive method which aims to describe a certain fact or reality that occurs during the filing of Value Added Tax (VAT) Restitution at PT CMT which is accompanied by PT Logistax Mitratama Solusi as a tax consultant who manages and assists PT CMT's taxation. The data collection carried out is observation, interviews, literature study, and documentation. The VAT Restitution Submission Procedure at PT CMT is carried out through a process of preparation stages, implementation stages, and evaluation stages. The implementation stage of PT CMT continues to carry out the restitution procedure in accordance with applicable regulations by being accompanied and directed by the tax consultant PT Logistax Mitratama Solusi as its tax consultant so that it can receive the disbursement of its restitution funds. In the preparation stage, PT Logistax Mitratama Solusi found obstacles in the form of a lack of physical documents in the purchase attachment belonging to PT CMT.